2020
DOI: 10.1007/s11605-019-04255-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Reconstruction Type After Gastric Resection Matters for Type 2 Diabetes Improvement?

Abstract: Type 2 diabetes mellitus (T2D) is a major cause of morbidity and mortality worldwide, associated to micro and macrovascular complications. A major risk factor for T2D is obesity. Gastrointestinal surgery was reported to facilitate glycemic control in type 2 diabetes (T2D) by reducing the needs for anti-diabetic medications. Non-obese T2D patients submitted to gastrointestinal surgery involving gastric resection and bypass of intestinal segments, arise as interesting model to dissect the gastro-intestinal (GI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Choi et al [19] compared the effects of R-Y and B-I reconstruction after DG on diabetes control in patients with early gastric cancer who had type 2 diabetes, and showed that R-Y reconstruction specifically ameliorated type 2 diabetes. Costa et al [20] also found that R-Y reconstruction significantly reduced BMI and ameliorated diabetes in obese patients with type 2 diabetes. Thus, R-Y reconstruction seems to be more effective at lowering blood glucose than other methods of reconstruction.…”
Section: Discussionmentioning
confidence: 91%
“…Choi et al [19] compared the effects of R-Y and B-I reconstruction after DG on diabetes control in patients with early gastric cancer who had type 2 diabetes, and showed that R-Y reconstruction specifically ameliorated type 2 diabetes. Costa et al [20] also found that R-Y reconstruction significantly reduced BMI and ameliorated diabetes in obese patients with type 2 diabetes. Thus, R-Y reconstruction seems to be more effective at lowering blood glucose than other methods of reconstruction.…”
Section: Discussionmentioning
confidence: 91%
“…In patients with digestive tract reconstruction after radical gastrectomy, changes in the structure of the digestive tract, the abundance and proportion of intestinal microbiota, and its influence on fatty acid metabolism and further intestinal homeostasis is a complex biological process affected by multiple factors. 12 , 48 It is still unclear whether SCFAs, as important metabolites of intestinal microbiota, regulate immune cells in this process to reduce excessive immune responses caused by changes in colonic symbionts and maintain homeostasis in the internal environment. As a product of the anaerobic fermentation of dietary fiber, SCFAs are important substances that regulate intestinal immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the role of digestive tract reconstruction in weight reduction and improvements in type 2 diabetes in obese patients with high BMIs. 11 , 12 However, the preoperative basic nutritional status is poor in some patients with advanced GC. Few studies have focused on the nutritional status of patients undergoing digestive tract reconstruction after radical gastrectomy, and the mechanism underlying the postoperative recovery stage remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%